(untitled) (Journal of Bio-Science, 2018)
The efficiency of physical factors (dry heat, low temperature and UV-radiation), leaf powders of Neem (Azadirachta indica A. Juss.), Bichuti (Flacourtia indica Merr.) and Parthenium weed (Parthenium hysterophorus L.) and two insecticides (Salvo and Amithrin plus) was evaluated against Callosobruchus maculatus (F.). For dry heat treatment, the calculated LD50 values for C. maculatus were 56.92, 54.26, 52.27, 50.76, 49.09, 50.55 and 29.59°C after 50, 60, 70, and 80 minutes, 24, 36, 48 h of treatment respectively, and the LD50 values were 58.61 and 5.18°C at 1 and 2 h for low temperature treatment respectively. LT50 values of the treatment of UV-radiation were 48.63, 29.89, 17.54, 11.11, 5.93 and 1.35 °C for the exposure period of 24, 36, 48, 60, 72 and 48 h respectively. The calculated LD50 values of leaf powder were 3.38, 3.15, 2.88, 2.45 and 2.40 mg cm-2 for A. indica, 3.91, 3.80, 3.55, 3.30, and 3.08 for F. indica, 12.11, 4.35, 1.86, 1.49, and 1.36 for P. hysterophorus after 12, 24, 36, 48 and 60 h of treatment respectively. The calculated LD50 values were 0.64, 0.33, 0.23, 0.04 and 0.008 mg cm-2 for Salvo and 0.35, 0.23, 0.09, 0.08 and 0.01 mg cm-2 for Amithrin plus at 12, 24, 36, 48 and 60 h respectively. The order of effectiveness of physical factors was dry heat >low temperature >UV-radiation. On the other hand, the order of toxicity of plant powders was F. indica >A. indica >P. hysterophorus. In case of insecticides it was Amithrin plus >Salvo. The findings suggest that physical factors and plant leaf powders can be used in integration with other bio rational approaches. J. bio-sci. 23: 57-65, 2015